Low expression of protocadherin7 (PCDH7) is a potential prognostic biomarker for primary non-muscle invasive bladder cancer - Lin, Ying-Li (Oncotarget, 2016)
Bladder cancer is a heterogeneous disease with outcome difficult to predict, and novel predictive biomarkers are needed. PCDH7, a member of protocadherins family, functions as tumor suppressor in several human cancers. The human PCDH7 gene is localized in chromosome 4p15, which is often inactivated in human cancers, including bladder cancer. The aim of this study was to investigate the clinical significance of PCDH7 expression in non-muscle invasive bladder cancer (NMIBC). PCDH7 expression was examined using immunohistochemical staining in 199 primary NMIBC tissues and 25 normal bladder epithelial tissues. Then the relationship between PCDH7 expression and clinicopathologic features was evaluated. Kaplan-Meier survival analysis and Cox analysis was used to evaluate the correlation between PCDH7 expression and prognosis. PCDH7 expression in NMIBC tissues was significantly lower than that in normal bladder epithelial tissues (P < 0.001). Low PCDH7 expression correlated with advanced grade (P = 0.021) and larger tumor size (P = 0.044). Moreover, patients with low PCDH7 expression have shorter recurrence-free survival (P < 0.001), progression-free survival (P = 0.007) and overall survival (P = 0.011) than patients with high PCDH7 expression. Low PCDH7 expression is an independent predictor of recurrence-free survival (multivariate Cox analysis: P = 0.007), progression-free survival (multivariate Cox analysis: P = 0.014) and overall survival (multivariate Cox analysis: P = 0.004). The findings indicate that low PCDH7 expression is a potential prognostic biomarker for primary NMIBC.